Placental co-transcriptional activator Vestigial-like 1 (VGLL1) drives tumorigenesis via increasing transcription of proliferation and invasion genes - Sonnemann, Heather M.; Pazdrak, Barbara; Nassif, Barbara; Sun, Yimo; Elzohary, Lama; Talukder, Amjad H.; Katailiha, Arjun S.; Bhat, Krishna; Lizée, Gregory (Frontiers in Oncology, 2024)
Vestigial-like 1 (VGLL1) is a co-transcriptional activator that binds to TEA domain-containing transcription factors (TEADs). Its expression is upregulated in a variety of aggressive cancer types, including pancreatic and basal-like breast cancer, and increased transcription of VGLL1 is strongly correlated with poor prognosis and decreased overall patient survival. In normal tissues, VGLL1 is most highly expressed within placental trophoblast cells, which share the common attributes of rapid cellular proliferation and invasion with tumor cells. The impact of VGLL1 in cancer has not been fully elucidated and no VGLL1targeted therapy currently exists. The aim of this study was to evaluate the cellular function and downstream genomic targets of VGLL1 in placental, pancreatic, and breast cancer cells. Functional assays were employed to assess the role of VGLL1 in cellular invasion and proliferation, and ChIP-seq and RNA-seq assays were performed to identify VGLL1 target genes and potential impact using pathway analysis. ChIP-seq analysis identified eight transcription factors with a VGLL1-binding motif that were common between all three cell types, including TEAD1-4, AP-1, and GATA6, and revealed ~3,000 shared genes with which VGLL1 interacts. Furthermore, increased VGLL1 expression led to an enhancement of cell invasion and proliferation, which was supported by RNA-seq analysis showing transcriptional changes in several genes known to be involved in these processes. This work expands our mechanistic understanding of VGLL1 function in tumor cells and provides a strong rationale for developing VGLL1targeted therapies for treating cancer patients.